Pushing past the plateau - Hamm, Joseph A. (Legal and criminological psychology, 2022)
In our target article (Hamm et al., Legal and Criminological Psychology, 2022), we propose a Concentric Diagram of Legitimacy as an organizing tool for legitimacy theory. In so doing, we hoped to stimulate a scholarly discussion about the state of the literature and the best avenues for pushing past the field’s current intellectual plateau. Six experts took us up on this call and provided three commentaries that push our thinking but, more importantly, identify important opportunities for advancing legitimacy theory. In our response here, we distil their rich insights into key criticisms which then lead to opportunities for future research.